Elternschaft und Familie jenseits von Heteronormativität und Zweigeschlechtlichkeit - Peukert, Almut; Teschlade, Julia; Wimbauer, Christine; Motakef, Mona; Holzleithner, Elisabeth (GENDER Sonderheft, 2020)
Rainbow family, insemination family, multi-parent family: These terms try to understand the phenomenon that parenthood and family are realized in diverse constellations. They are caught between empirical diversity and societal norms and norms. The articles in the special issue explore the family forms of lesbian two-parent families, trans * and co-parenting, non-monogamous relationship networks as well as queer relationship networks in the context of escape .; Same-sex parenting, co-parenting, blended family: These terms try to capture the phenomenon that parenthood and family are realized in manifold constellations. They are caught between empirical diversity and social notions of norm and normality. The articles in this special issue explore the family forms of lesbian two-parent families, trans * and co-parenthood, non-monogamous relationship networks, and queer relationship networks in a refugee context.